Türkçenin yabancı dil olarak öğretiminde akademik yazma yeterliklerinin geliştirilmesine yönelik bir çalışma - Yılmaz, Esra (My University, 2022)
Türkiye’nin uluslararası alanda öneminin artmasıyla birlikte akademik eğitim almak amacıyla ülkemize gelen yabancı öğrencilerin sayısında da artma olmuştur. Bu araştırmada, ülkemize gelen yabancı uyruklu öğrencilerin akademik yazma becerisinin geliştirilmesi amaçlanmıştır. Araştırma, nitel araştırma yöntemlerinden biri olan eylem araştırması ile yapılmıştır. Araştırmanın çalışma grubunu, 2020- 2021 akademik yılında İstanbul Üniversitesi Dil Merkezinde akademik Türkçe kursu alan 16 öğrenci oluşturmaktadır. Araştırmacı tarafından öğrencilerin akademik becerilerinin gelişimine yönelik materyaller oluşturulmuş ve bu materyaller akademik Türkçe kursu sürecinde öğrencilere uygulanmıştır. Uygulamaya ilişkin veriler gözlem, araştırmacı günlüğü, video ve ses kayıtları, yazma becerisi kontrol listesi aracılığıyla toplanmıştır. Elde edilen nitel veriler içerik analizi ile nicel veriler ise spss programları ile yorumlanmıştır. Nitel verilerin yorumlanmasını kolaylaştırmak amacıyla sayısal ifadeler ve tablolardan sıklıkla faydalanılmıştır. Toplanan veriler ışığında oluşturulan materyallerin öğrencilerin akademik yazma becerilerinin gelişmesine katkı sağladığı gözlemlenmiştir. Ayrıca bu çalışmada oluşturulan materyallerin, akademik Türkçe derslerine yönelik hazırlanacak olan içeriklere bir örnek sunması dolayısıyla alanda çalışan kullanıcılara yol gösterici olacağı düşünülmektedir.

Due to Turkey’s increasing importance in the international arena, the number of students coming to Turkey to receive academic education has also increased. The aim of this study is to improve the level of academic writing skills of international students in Turkey through the use of the action research method. The research universe of the study is a group of higher education students who are learning Turkish as a foreign language and have completed the C1 level. The research sample of the study consists of 16 students who were studying academic Turkish at the İstanbul University Language Center in 2020-2021. Class materials focused on the development of students’ academic skills were created by the researcher and were applied to the students during the course term. The research data were collected through observations, daily note taking, videos, recordings and written work was assesed through the use of a previously prepared rubric of writing skills. The objective data collected during the research was interpreted using internal analysis and SPSS programs. Tables and digital datas are frequently used to simplify the data interpretation. According to the collected data, class materials contributed to the development of academic writing skills of the students. It is hoped that the results of this study, and the materials which were created and used in this research will be of use to professionals in the field of Teaching Turkish as a Foreign Language.
A study on the development of academic writing skills in teaching turkish as a foreign language
Keywords: academic language; academic Turkish; akademik dil; akademik Türkçe; Gramer; Grammar; Öğrenim ve öğretim; Study and teaching; Teaching Turkish as a foreign language; Turkish language; Türk dili; Yabancılara Türkçe Öğretimi